Chambers Biographical Dictionary - John Bakewell (Chamberd Harrap publishers, 2011)
Packed with over 18,000 biographies, Chambers Biographical Dictionary offers concise, authoritative and fascinating entries on all the people you'll ever need to know about. The most comprehensive and readable single-volume biographical dictionary available. - Discover kings, queens, crooks, criminals, politicians, bankers and everyone in between. - Check up on great achievements and great failures. - Find out who did what to whom. - Thousands of suggestions for further reading. - Contains more biographies than any other reference work of its type. - International and historical coverage of all areas of human achievement including the arts, science, technology, sport, politics, philosophy and business. - Meticulously researched and expertly written.